The impact of wind catchers on thermal comfort and indoor air quality: An analysis of subtropical climate for summer and winter - Khalid, Asma; Dahlan, Nur Dalilah; Abas, Mohd Firdaus; Ahmad, Kamarul Arifin; Shahidan, Mohd Fairuz (SAGE Publications, 2025)
Employees spend 8 h of the day with a minimum of 40 h a week in offices. The office design, furniture and ventilation modes cause high energy consumption, pollutants and sick building syndrome amongst employees. Based on ASHRAE standards and WHO guidelines, the study evaluated offices for the temperature, humidity, PM2.5, CO2 and employees’ subjective assessment. The offices met humidity standards except for the Punjab Civil Secretariat (PCS) (61.9%, ± 0.1) and the Directorate of Public Instruction (54.1%, ± 0.3) in the summer and winter respectively. The concentrations of CO2 in offices were unhealthy for both seasons except the PCS (697.3 ppm, ± 9.2) and Punjab Skill Development Authority (838.9 ppm, ± 13.3). The mean PM2.5 concentration for offices was unhealthy during summer (28.4–53.7 μg/m3) and hazardous in winter (178–233.7 μg/m3). The one-way ANOVA of employees’ subjective assessment showed that the results were significant (p < 0.05) for indoor air quality, thermal comfort satisfaction, preference, health effect, filtration and wind catcher preference, for two seasons and within ventilation modes. The familiarity with wind catcher designs was insignificant (p > 0.05) but employees preferred their modern applications. The comfort indexes showed that the Governor House (PMV -0.04, PPD 5%) met the thermal comfort standards during winter.